1987
DOI: 10.1111/j.1471-4159.1987.tb05662.x
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine and Reserpine Deplete Brain Biogenic Amines and Alter Blow Fly Feeding Behavior

Abstract: HPLC with electrochemical detection was used to determine the levels of p-hydroxyphenylethanolamine (octopamine), 3,4-dihydroxyphenylethylamine (dopamine), and 5-hydroxytryptamine (5-HT) in the brains of control, reserpine, and d-amphetamine-treated blow flies, Phormia regina Meigen. Parallel studies were carried out to assess the effects of the two drugs on fly feeding behavior, measured as mean acceptance threshold: the minimum sucrose concentration to which the average fly in a population will respond by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Other pharmacological agents commonly used in vertebrates for 5-HT depletion, for example, pchlorophenylalanine, reserpine, and 5,7-dihydroxytryptamine, were not tried. The selectivity and efficacy of these agents when used in insects varies widely (Omar et al, 1982;Sloley and Owen, 1982;Pandey et al, 1983;Brookhart et al, 1987). Also, when these agentsdo cause a depletion of CNS 5-HT in invertebrate preparations, in most cases it is a partial and short-term depletion, not the total depletion for the long durations needed for our experiments in Mundzica (Glover and Kramer, 1982;Lent and Dickinson, 1984;Murphy et al, 1984;Nassel and Elekes, 1985;Gadotti et al, 1986;Orchard, 1990, 1993).…”
Section: Pharmacological Ablationmentioning
confidence: 96%
“…Other pharmacological agents commonly used in vertebrates for 5-HT depletion, for example, pchlorophenylalanine, reserpine, and 5,7-dihydroxytryptamine, were not tried. The selectivity and efficacy of these agents when used in insects varies widely (Omar et al, 1982;Sloley and Owen, 1982;Pandey et al, 1983;Brookhart et al, 1987). Also, when these agentsdo cause a depletion of CNS 5-HT in invertebrate preparations, in most cases it is a partial and short-term depletion, not the total depletion for the long durations needed for our experiments in Mundzica (Glover and Kramer, 1982;Lent and Dickinson, 1984;Murphy et al, 1984;Nassel and Elekes, 1985;Gadotti et al, 1986;Orchard, 1990, 1993).…”
Section: Pharmacological Ablationmentioning
confidence: 96%
“…Reserpine interferes with the vesicular uptake of monoamines in nerve terminals and has been widely used to block neurotransmission by monoamines. In the blowfly, reserpine decreases the brain level of octopamine more readily than that of dopamine or serotonin (Brookhart et al, 1987). Applied to the honeybee, immunohistochemical methods showed that reserpine reduces monoamines in the brain below detection levels (Braun and Bicker, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…Reserpine depletes the brain of monoamines (Brookhart et al, 1987;Braun and Bicker, 1992). The strong reduction in the intensity of the proboscis extension response to sucrose solution caused by reserpine (Braun and Bicker, 1992) was used to monitor the success of this treatment.…”
Section: Modulation Of Pka Activity In the Antenna1 Lobe By In Vivo Smentioning
confidence: 99%
“…It is well known that reserpine administration in mammals reduces the levels of brain amines (39), leading to characteristic alterations in behaviour. Several studies in insects indicate that reserpine also non-specifically reduces the levels of serotonin, octopamine and dopamine from the central nervous system (5,20,41,46). PCA is a potent neurotoxin which has been shown to induce rapid release and depletion of 5-HT in the brain of rats (48).…”
mentioning
confidence: 99%